Effect of heat pump drying temperature on moisture migration characteristics and quality of instant Tremella fuciformis - Li Wu; Shouhui Chen; Yibin Li; Wei Xie; Baosha Tang (Current Research in Food Science)
Low-field nuclear magnetic resonance (LF-NMR) was used to analyze the moisture migration characteristics and water distribution of instant Tremella fuciformis (ITF) during heat pump drying at 35 °C, 45 °C and 55 °C. A fuzzy mathematical evaluation method was then used to investigate the effect of heat pump drying temperatures (35 °C, 45 °C and 55 °C) on the quality of ITF. Based on the screened appropriate temperature of 45 °C, the thin layer heat pump drying curve and drying rate curve of ITF were drawn, then four mathematical models were tested based on the coefficient of determination (R2). The result showed three water components (bound water (T21), immobilized water (T22), and free water (T23)) in ITF before drying. During the drying process, the heat pump drying of ITF was carried out gradually from the outer to the inner. The sensory total score (77.66 ± 6.57), rehydration ratio (4803.00 ± 90.00%), and viscosity (45.01 ± 3.61 Pa s) of ITF in heat pump drying at 45 °C were the best. The optimal drying temperature of 45 °C was obtained by the fuzzy comprehensive evaluation with the highest comprehensive score of 77.85%. With the prolongation of drying time, the water content of ITF showed a gradual decreasing trend, and the water content was controlled to below 8.51% after 6 h. The drying curve shows that the drying phase of the ITF is divided into three phases, including preheat, constant speed and deceleration. The drying speed first increases, remains constant in the middle and then decreases. Among the four models tested, the cubic regression equation aligned with the change rule of the ITF drying curve (R2 = 0.99397). By studying the effect of drying temperature on the moisture migration characteristics and the quality of ITF, we aim to provide more data support for the production of T. fuciformis.